Low Energy N5+ Ion Induced Modification on the Flower-Like ZnSe Nanostructured Thin Films: Structural and Optical Properties - Bakiyaraj1, G.; Krishna2, J.B.M.; Taki3, G.S.; Dhanasekaran4, R. (Asian Journal of Chemistry, 2013)
Flower-like zinc selenide nanstructured thin films were deposited by chemical bath deposition method. The as-deposited ZnSe thin films were implanted with 45 keV N5+ ions at different doses ranging from 5 × 1015 to 5 × 1016 ions/cm2. X-ray diffraction studies confirmed that all the films have a nanocrystalline nature with cubic structure. HRSEM images of the films revealed the formation of ZnSe nanoflowers of diameter range 100-200 nm and the thickness of petals about 5-10 nm. After ion implantation all of these flowers were sintered and formed larger particles. The optical band gap of the film is decreased from 2.83 to 2.60 eV after implantation probably due to defect/disorder induced band-tailing, creation of impurity states and improvement in crystallite size.